2017
DOI: 10.3390/pharmaceutics9040041
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Oral Drug Absorption: Mini Review on Physiologically-Based Pharmacokinetic Models

Abstract: Most marketed drugs are administered orally, despite the complex process of oral absorption that is difficult to predict. Oral bioavailability is dependent on the interplay between many processes that are dependent on both compound and physiological properties. Because of this complexity, computational oral physiologically-based pharmacokinetic (PBPK) models have emerged as a tool to integrate these factors in an attempt to mechanistically capture the process of oral absorption. These models use inputs from in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
84
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(84 citation statements)
references
References 51 publications
0
84
0
Order By: Relevance
“…Food can affect GI physiological factors such as gastric emptying time, acid secretion, blood flow, intestinal motility, bile and enzyme secretion. [8][9][10][11][12] The effectiveness of captopril was assessed by evaluating the difference (Δ) of systolic blood pressure (SBP) and diastolic blood pressure (DBP) in mmHg units seen from the median values. We found out that the reduction of SBP in group who consumed captopril on an empty stomach and after meal was 30 mmHg and 25 mmHg, respectively (p<0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Food can affect GI physiological factors such as gastric emptying time, acid secretion, blood flow, intestinal motility, bile and enzyme secretion. [8][9][10][11][12] The effectiveness of captopril was assessed by evaluating the difference (Δ) of systolic blood pressure (SBP) and diastolic blood pressure (DBP) in mmHg units seen from the median values. We found out that the reduction of SBP in group who consumed captopril on an empty stomach and after meal was 30 mmHg and 25 mmHg, respectively (p<0.05).…”
Section: Resultsmentioning
confidence: 99%
“…The low oral bioavailability has become a common problem in drug design, since it may pose failure to a new drug in a clinical trials, eventhough the compounds have high eficacy in in vitro and/or in vivo tests (Kim et al, 2014). This may incure problem faced by scientists in the pharmaceutical industry (Lin & Wong, 2017). Therefore, oral bioavailability of a compound is essential to be taken into account when predicting the compound as a drug candidate.…”
Section: Discussionmentioning
confidence: 99%
“…About 500 µL blood samples were collected at 0. 5,1,2,3,4,5,6,8,10,12,16,20,24,30 and 36 h into heparinized tubes after the intragastric administration of MHO7. All blood samples were immediately centrifuged at 8000 g for 5 min and the resulting plasma was transferred and then processed as described in sample preparation for the analysis by LC-MS/MS.…”
Section: Pharmacokinetic Studies Assaymentioning
confidence: 99%
“…Although the family of Ophs have shown anticancer activity in some cancer cell lines [5], no toxicity and pharmacokinetics studies have been reported on these compounds. Due to the convenient administration, the oral route of drug administration is the most common approach comparing with injections (intravenous, intramuscular, and subcutaneous) or inhalation administration [12,13]. Drugs dissolve in the gastrointestinal tract after oral administration and then distribute throughout the body, which depends on the solubility in different pH environments of the compounds [13].…”
Section: Introductionmentioning
confidence: 99%